2018
DOI: 10.1146/annurev-orgpsych-032117-104613
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Measurement in the Organizational Sciences: A Review and Recommendations for Future Use

Abstract: We review recent literature in the organizational sciences that uses some form of physiological measurement. We organize our review in terms of the underlying constructs that physiological measures were intended to assess. The majority of such constructs represents stress, health, or arousal, although these constructs are often studied in an attempt to understand a diverse set of other phenomena. The majority of the studies we discuss use peripheral measures of the autonomic nervous system or biological indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 105 publications
0
51
0
Order By: Relevance
“…To adequately assess how the three M s work in organizations necessitates new methods or a wider application of existing tools. Our call to study hormonal transitions is consistent with calls for physiological research in organizational science (Ganster et al, 2018; Ganster & Rosen, 2013), and we particularly need to link objective indicators of hormone levels and bodily changes with work outcomes to determine whether hormonal changes or self/societal beliefs are having career costs (e.g., Motro et al, 2019). We especially call for within-person methods (e.g., Gabriel et al, 2018; Motro et al, 2019) to identify covariation of female hormonal changes (i.e., estrogen, oxytocin) and physiological indicators (i.e., galvanic skin response) with social judgments and task performance.…”
Section: Implications Of the Three Ms For Organizational Sciencementioning
confidence: 82%
See 1 more Smart Citation
“…To adequately assess how the three M s work in organizations necessitates new methods or a wider application of existing tools. Our call to study hormonal transitions is consistent with calls for physiological research in organizational science (Ganster et al, 2018; Ganster & Rosen, 2013), and we particularly need to link objective indicators of hormone levels and bodily changes with work outcomes to determine whether hormonal changes or self/societal beliefs are having career costs (e.g., Motro et al, 2019). We especially call for within-person methods (e.g., Gabriel et al, 2018; Motro et al, 2019) to identify covariation of female hormonal changes (i.e., estrogen, oxytocin) and physiological indicators (i.e., galvanic skin response) with social judgments and task performance.…”
Section: Implications Of the Three Ms For Organizational Sciencementioning
confidence: 82%
“…Though part of women’s health, the three M s are rarely mentioned in occupational health research, despite the goal of “protecting and promoting the safety, health and well-being of workers” (National Institute for Occupational Safety and Health, 2013). Furthermore, a recent review on physiological measurement in organizational science mentioned no research on estrogen, progesterone, or oxytocin (Ganster, Crain, & Brossoit, 2018), highlighting a disconnect between women’s health and occupational health frameworks. As a comparison, testosterone, the hormone more prevalent in men, can be found in research on stress and leadership (Bendahan, Zehnder, Pralong, & Antonakis, 2015; Ronay & Carney, 2013).…”
Section: Implications Of the Three Ms For Organizational Sciencementioning
confidence: 99%
“…Stress reactions are characterized by negative mood or emotions, that is, negative affect (Lazarus, 1993), and many studies use indicators of negative affect to assess stress (e.g., Cohen-Charash & Spector, 2001;McIntyre et al, 2008). Acute stress reactions typically are associated with arousal (Ganster et al, 2018;McEwen & Wingfield, 2003), indicated by constructs such as anxiety, nervousness, tension, or anger/resentment (Cropanzano et al, 2003;Posner et al, 2005;Warr, 2007), which represent the "distress quadrant" of the emotional circumplex (Van Katwyk et al, 2000). Negative affective reactions to stress may also be combined with low arousal, indicated by sadness or depression (Ganster & Rosen, 2013;Van Katwyk et al, 2000).…”
Section: Outcome Variables I: Negative Affectmentioning
confidence: 99%
“…Wearable sensors are one source of 'big data' that have attracted considerable attention from social scientists. Different sensor types provide access to previously hard-to-observe phenomena such as the heart-rate, small body movements and skin resistance, among many others (Foster, 2019;Ganster et al, 2018). Sensors gather high-resolution data on the oftenunconscious bodily activity that underlies and to a large degree conditions the conscious social behavior that has been the traditional focus of social scientists.…”
Section: Wearable Sensor Proximity Measurements In Organizational Resmentioning
confidence: 99%